Assessment of left ventricular mass by cardiovascular magnetic resonance. - Myerson, S; Bellenger, N; Pennell, D (2002)
Left ventricular hypertrophy is associated with significant excess mortality and morbidity. The study and treatment of this condition, in particular the prognostic implications of changes in left ventricular mass, require an accurate, safe, and reproducible method of measurement. Cardiovascular magnetic resonance is a suitable tool for this purpose, and this review assesses the technique in comparison with others and examines the clinical and research implications of the improved reproducibility.